Nature of Feedback and Interaction in Online Courses during COVID-19 - Mohammed Farrah; Riham Abdalnabi; Amal Sider (RIRAI Publisher, 2022)
Feedback and interaction are essential parts of the learning process. No effective teaching and learning can take place without proper interaction and effective feedback. This study investigates the nature of feedback and interaction in online courses during COVID-19 during the academic year 2020/2021. The researchers employed both qualitative and quantitative research methods to achieve the purpose of this study. The study sample consisted of 115 students who are majored in the English language at Hebron University Moreover, four instructors were interviewed regarding the nature of interaction and feedback during COVID-19. The analyzed inputs of the questionnaire have shown that most of the students did not practice E-learning before, and they have internet connection in their home. Furthermore, most of the students agreed that face-to-face classes are better and more valuable especially in terms of interaction, online learning is considered as an effective way to maintain the communication during the pandemic and the nature of feedback given from instructors affect students’ interaction. Moreover, instructors can motivate students to interact with them and with other students during online sessions. It is important to mention that online assessment is criterion that instructors need to take into consideration. In addition to students' attitudes towards online interaction and feedback, teachers during interviews expressed their preference to face to face learning, and they think that interaction and feedback during online sessions are different and less fruitful than face-to-face teaching. At the end of this study, the researchers suggested some recommendations that may be achieved to improve the nature of interaction and feedback during the current situation.